Visually Impaired Drivers Who Use Bioptic Telescopes: Self-Assessed Driving Skills and Agreement With On-Road Driving Evaluation - Owsley, Cynthia (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. To compare self-assessed driving habits and skills of licensed drivers with central visual loss who use bioptic telescopes to those of age-matched normally sighted drivers, and to examine the association between bioptic drivers' impressions of the quality of their driving and ratings by a “backseat” evaluator. METHODS. Participants were licensed bioptic drivers (n = 23) and age-matched normally sighted drivers (n = 23). A questionnaire was administered addressing driving difficulty, space, quality, exposure, and, for bioptic drivers, whether the telescope was helpful in on-road situations. Visual acuity and contrast sensitivity were assessed. Information on ocular diagnosis, telescope characteristics, and bioptic driving experience was collected from the medical record or in interview. On-road driving performance in regular traffic conditions was rated independently by two evaluators. RESULTS. Like normally sighted drivers, bioptic drivers reported no or little difficulty in many driving situations (e.g., left turns, rush hour), but reported more difficulty under poor visibility conditions and in unfamiliar areas (P < 0.05). Driving exposure was reduced in bioptic drivers (driving 250 miles per week on average vs. 410 miles per week for normally sighted drivers, P = 0.02), but driving space was similar to that of normally sighted drivers (P = 0.29). All but one bioptic driver used the telescope in at least one driving task, and 56% used the telescope in three or more tasks. Bioptic drivers' judgments about the quality of their driving were very similar to backseat evaluators' ratings. CONCLUSIONS. Bioptic drivers show insight into the overall quality of their driving and areas in which they experience driving difficulty. They report using the bioptic telescope while driving, contrary to previous claims that it is primarily used to pass the vision screening test at licensure.